I think it is true but I am not 100% sure thought but good luck
Answer:
Step-by-step explanation:
yhgvuvuvuynfyftfjtgfyjgfftyf
Answer:
B
Step-by-step explanation:
+ 6 = x ( subtract 6 from both sides )
= x - 6 ( square both sides )
x = (x - 6)² ← expand using FOIL
x = x² - 12x + 36 ( subtract x from both sides )
0 = x² - 13x + 36 , that is
x² - 13x + 36 = 0 ← in standard form
(x - 4)(x - 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 4 = 0 ⇒ x = 4
x - 9 = 0 ⇒ x = 9
As a check
Substitute these values into the equation and if both sides are equal then they are the solutions.
x = 4
left side = + 6 = 2 + 6 = 8
right side = x = 4
Since 8 ≠ 4 then x = 4 is an extraneous solution
x = 9
left side = + 6 = 3 + 6 = 9
right side = x = 9
Thus the solution is x = 9 → B
Answer:
5 bars
Step-by-step explanation:
340-(55+55)
230÷40
5.75
Answer:
<u>66.22 </u>times 10=662.2
<u>4.03 </u>times 100=403
<u>0.108 </u>times 1000=108
Step-by-step explanation:
662.2 ÷ 10
403 ÷ 100
108 ÷ 1000